The Mistaken Biography of the Riga Vase or Overglaze Decoration Techniques as an Aspect in the Attribution of a Porcelain Artefact - Brants, Inese (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
This research examines one of the most remarkable exhibits of the Riga Porcelain Museum – the Riga Jubilee Vase made in J. C. Jessen's porcelain factory in honour of the 700th anniversary of Riga. In 1901, the Riga Jubilee Vase was displayed for the first time – in the Riga Anniversary Exhibition of Industry and Crafts. The impressive porcelain object was kept in the Riga Porcelain Factory's museum until 2001, but after the factory's closure it became the pride of the Riga Porcelain Museum's permanent exhibition. Upon reading the article on this outstanding artefact in the 2012 February issue of the magazine Illustrated History, despite it being prepared in cooperation with the Riga Porcelain Museum, reasonable doubt arose about the accuracy of the description of the technical execution of the vase. The article Impressive dedication to Riga reads: 'The red-brown selenium ground and matte gold ornamental band creates a somewhat heavy impression, uncharacteristic for porcelain.' The study aims to find out whether the assertion 'the red-brown selenium ground' is true and eliminate some of the inaccuracies in the use of terms. The research is based on the analyses of the Riga Porcelain Museum's inventory of the Riga Jubilee Vase; the chemical composition data of red porcelain overglaze paints and their technical particularities; an experiment, testing the interaction of cadmium / selenium and iron-containing red overglazes with gilding; and consultations with leading experts – Dace Bluma, formerly employed in the Riga Porcelain Factory, and Sergei Rusakov from the Imperial Porcelain Factory in St. Petersburg. The acquired data allows conclude that iron-containing rather than selenium-containing red paint has been used for the Riga Jubilee Vase grounding and the painting technique's description in the museum's inventory is incorrect.